2023
DOI: 10.3389/fimmu.2023.1182299
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced rectal cancer with dMMR/MSI-H may be excused from surgery after neoadjuvant anti-PD-1 monotherapy: a multiple-center, cohort study

Abstract: ObjectiveExamine patients with locally advanced rectal cancer (LARC) with deficient mismatch repair (dMMR) or microsatellite instability-high (MSI-H) who received neoadjuvant immunotherapy (nIT), and compare the outcomes of those who chose a watch-and-wait (WW) approach after achieving clinical complete response (cCR) or near-cCR with those who underwent surgery and were confirmed as pathological complete response (pCR).MethodsLARC patients with dMMR/MSI-H who received nIT were retrospectively examined. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The role of dostarlimab, another antiPD-1 checkpoint inhibitor, as neoadjuvant treatment in locally advanced rectal cancer also showed a remarkable 100% clinical complete response (cCR), allowing these patients to spare chemoradiotherapy and surgery, with no relapse evidence during follow up. These results have been confirmed in a 20-patient retrospective study: a 90% cCR was observed and pCR was confirmed in all the 11 patients that underwent surgery; the other 7 patients chose a watch-and-wait strategy, with no local or distant recurrence observed in neither of the groups ( 28 ). Interestingly, none of these trials are evaluating the role of immunotherapy as conversion therapy in oligometastatic disease and data from patients that could be elected for surgery in the metastatic trials published were censored.…”
Section: Current State Of the Art Challenges And Future Directions: D...mentioning
confidence: 57%
“…The role of dostarlimab, another antiPD-1 checkpoint inhibitor, as neoadjuvant treatment in locally advanced rectal cancer also showed a remarkable 100% clinical complete response (cCR), allowing these patients to spare chemoradiotherapy and surgery, with no relapse evidence during follow up. These results have been confirmed in a 20-patient retrospective study: a 90% cCR was observed and pCR was confirmed in all the 11 patients that underwent surgery; the other 7 patients chose a watch-and-wait strategy, with no local or distant recurrence observed in neither of the groups ( 28 ). Interestingly, none of these trials are evaluating the role of immunotherapy as conversion therapy in oligometastatic disease and data from patients that could be elected for surgery in the metastatic trials published were censored.…”
Section: Current State Of the Art Challenges And Future Directions: D...mentioning
confidence: 57%
“…The multicenter cohort study by Yang et al investigated the management of dMMR or MSI-H LARC following neoadjuvant anti-PD-1 monotherapy, exploring the possibility of avoiding surgery in the case of cCR [34]. In fact, 7 of 20 enrolled patients with cCR adopted a W&W strategy.…”
Section: Mismatch Repair-deficient (Dmmr) or Microsatellite Instabili...mentioning
confidence: 99%
“…Considering the remarkable efficacy of immunotherapy in colorectal cancer, at the 2022 ASCO Annual Meeting, Cercek et al demonstrated that a 100% cCR rate could be achieved with dostarlimab alone for patients with dMMR/MSI-H (115). Additionally, Yang et al used different types of PD-1 inhibitors, including pembrolizumab, sintilimab, and tislelizumab, to treat 20 LARC patients with dMMR/MSI-H. As a result, 90% of the patients experienced CR, of whom 11 achieved pCR postoperatively, and the remaining 7 had cCR or near-cCR, with 2year DFS and OS rates of 100% (116). Further, Chen et al found that 12 out of the 16 patients in their study achieved CR, further demonstrating the significant efficacy of immuno-monotherapy as a neoadjuvant treatment for LARC patients with dMMR/MSI-H (117).…”
Section: Combination With Immunotherapymentioning
confidence: 99%